Shaping ability of three heat-treated NiTi systems in Vertucci's type III root canals of mandibular incisors: An ex vivo study - Leal, Renata Maira de Souza; Copelli, Felipe Andretta; Pinto, Jáder Camilo [UNESP]; Tanomaru-Filho, Mario [UNESP]; Duarte, Marco Antonio Hungaro; Cavenago, Bruno Cavalini (Springer Nature, 2024)
Introduction: The anatomical configuration classified as Vertucci's type III is described as the second most prevalent in mandibular incisors. Methods: Thirty-six Vertucci's type III mandibular incisors were evaluated by micro-computed tomography (micro-CT) and divided into 3 groups (n = 12) according to the root canal preparation protocol (HyFlex CM [HCM], HyFlex EDM [HEDM], and Sequence Rotary File [SRF]). The teeth were scanned before and after performing 0.25 mm and 0.40 mm apical diameter preparations. The canal volume, dentin thickness, percentage of accumulated debris and untouched canal areas, transportation, and centering ability were measured. The data were statistically analyzed by ANOVA, Tukey, Kruskal-Wallis, and Dunn tests (P < 0.05). Results: The volume increase was more evident in the apical third. After 0.40 mm preparation, the SRF system provided a higher reduction (P < 0.05) in dentin thickness on the buccal surface 1 mm from the apex. There was higher canal transportation in the bucco-lingual direction. The 0.40 mm apical preparation reduced the percentage of untouched canal areas. The apical third had the highest percentage of untouched canal areas. The cervical third had the lowest volume of accumulated debris. Conclusions: Increasing the apical preparation to a diameter of 0.40 mm with the HCM, HEDM, and SRF systems in Vertucci's type III root canals of mandibular incisors proved to be safe and effective, reducing untouched canal areas. Clinical relevance: Root flattening can be intense to the point of generating a root canal bifurcation. Despite the decrease in the root canal diameter, a greater enlargement of the apical region is necessary and safe.
Keywords: Canal transportation; Dentin thickness; Mandibular incisors; micro-CT; Untouched canal areas